1996
DOI: 10.1103/physrevb.54.6700
|View full text |Cite
|
Sign up to set email alerts
|

Photoemission and x-ray absorption study of superconducting and semiconductingBa1xKxBi

Abstract: Semiconducting Ba 0.9 K 0.1 BiO 3 and superconducting Ba 0.6 K 0.4 BiO 3 single crystals cleaved in situ have been studied by core level and valence band photoelectron spectroscopy and O K edge x-ray absorption spectroscopy. It was found that the general shape of the valence band spectrum agrees with the shape predicted by band structure calculations, but the intensity near the Fermi level was lower in the experimental spectrum as compared to the calculated. The O K edge spectra showed that the metallic phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Salem-sugui et al [17] observed a prepeak in the O 1s XAS spectra for BKBO with x = 0.0, 0.2 and 0.4 and a continuous change across the transition x ∼ x c was observed. Qvarford et al [18] also reported result for x = 0.1 and 0.4 and obtained similar results. A systematic study covering a wider concentration range, however, has been lacking.…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…Salem-sugui et al [17] observed a prepeak in the O 1s XAS spectra for BKBO with x = 0.0, 0.2 and 0.4 and a continuous change across the transition x ∼ x c was observed. Qvarford et al [18] also reported result for x = 0.1 and 0.4 and obtained similar results. A systematic study covering a wider concentration range, however, has been lacking.…”
Section: Introductionsupporting
confidence: 73%
“…7 (b), (c) and (d), we also show the results of the Bi 4f 7/2 , O 1s and Ba 3d core-level XPS spectra, respectively. According to the high resolution XPS study [18], the lineshapes of the core levels of the metallic BKBO are not single peaks but of multi-components with an energy-loss structure on the high binding energy (E B ) side. In fact, the core-level spectra in the metallic phase (particularly, x = 0.50 and 0.60) show somewhat broader peak widths than those in the insulating phase.…”
Section: Electronic Structure Near the Fermi Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Before the photo-emission experiments, the oxygen-deficient samples were created by annealing superconducting single crystals (T c ϭ25 K) at 480°C for 1 h in an atmosphere at a pressure of 10 Ϫ2 torr. No superconductivity was observed after the annealing.…”
Section: Methodsmentioning
confidence: 99%
“…Previous attempts to address the Bi 4 f asymmetry have also been made by means of crystal defects, contaminations gathered at grain boundaries and chemical inhomogeneity of the samples. 13 Because of the reported variations in the Bi 4 f asymmetry from sample to sample with the same nominal composition, 13 it is important to consider the quality of the topmost layers of the single crystals when interpreting the Bi 4 f asymmetry.…”
Section: Introductionmentioning
confidence: 99%